DEMOGRAPHIC PROFILE, GLYCEMIC CONTROL AND TREATMENT PATTERNS OF TYPE 1 DIABETES PATIENTS IN CENTRAL PAHANG - Keong, See Chee; Jasmiad, Nurbadriah; Ismail, Ilham (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The burden of Type 1 diabetes (T1D) care in adulthood is often overshadowed by the increasing Type 2 diabetes prevalence. In addition to the complexity of transitional care from adolescence to adulthood, there are multiple barriers to the care of these patients. Identifying these barriers is crucial to facilitate creating personalized and focused care for T1D patients. METHODOLOGY This was a cross-sectional study recruiting all T1D patients who consulted in endocrinologist-led diabetes clinics in secondary and tertiary hospitals in Central Pahang, Malaysia. This included coverage areas of Bentong, Temerloh, Bera, Jengka, and Jerantut in Pahang. The study aimed to determine the demographic data, glycemic control, diabetes complications, and treatment patterns in T1D patients. Patient’s electronic medical records were retrieved for data collection. RESULTS Fifty-eight patients were recruited into the study, with female predominance (63.8%), and the majority were of Malay ethnicity (67.2%). The mean age of the patients was 25.26, (SD = 7.5) with a mean age at diagnosis of 16.98 (SD = 6.9). The majority had a duration of illness of 7 years. Almost 66% of patients had prior testing for autoantibodies and c-peptide as diagnostic confirmation. Fifty percent of patients had childhood-onset diabetes, presenting early with diabetic ketoacidosis. For diabetes complications, 24.1% of patients had nephropathy, while 12.1% had diabetic retinopathy. Up to 10.3% had documented hypoglycemia, and 8.6% had DKA in the past six months. Despite poor glycemic control, there was still a statistically significant reduction of HbA1c from baseline compared to the latest follow up (10.93% vs 9.92%, p <0.01). Only 32.1% of patients at the latest follow-up had HbA1c less than 8.5%. The mean total daily insulin usage was 0.84 SD 0.3 u/ kg/day. Only 17.2% of T1D patients had prior exposure to continuous glucose monitoring utilization. CONCLUSION Enrolment in a specialized T1D clinic is important to deliver an appropriate and targeted approach to T1D patients. The poor control of T1D patients in this cohort reflects the barriers to care including treatment access, adequacy of glucose monitoring, disease understanding and peer and family support. Technology-based intervention in T1D patients is still underutilized and concerted effort to incorporate technology into treatment needs to be intensified.